Influential Factors on Pharmacist Profession- Related Errors: a Community Pharmacy Approach: Pharmacist profession-related errors - Sarhangi, Nima; Nikfar, Shekoufeh; Zakerian, Seyed Abolfazl; Afzali, Monireh (Iranian Journal of Pharmaceutical Sciences, 2021)
Community pharmacy is one of the most important control stations in pharmacotherapy. Hence, Pharmacist mistakes may cause or lead to inappropriate medication use by patients or even permanent harm. Therefore, quality control in pharmacists’ practice is a safety issue and in addition has an added importance for society. This study has been designed to investigate the relationship between age, gender, shift work of pharmacists and the frequency of errors to determine possible defect and planning for them. Job descriptive and analysis were done using Hierarchical Task Analysis (HTA). The study population was observed directly and all the defined mistakes were recorded. The collected data were analyzed using regression and two-sided, chi-square analysis. The pharmacists supervised for 64 determinate mistakes and 3968 mistakes were recorded with a rate 36.7%. Based on the results, occurrence of mistakes are associated with shift work, age, and gender of pharmacists. There are significant increases in incidence of occupational errors in afternoon and night shifts, male population, over 40 years’ old population and long shift. Considering the relationship between pharmacist profession- related error and shift conditions or some of the demographic factors, it seems that further systematic evaluation on community pharmacy administration is necessary.